The role of weather in the narrative of the Second Punic War - Matusiak, Patrycja (Armia kontra natura, 2020)
The purpose of the article is to present the role of natural weather phenomena that were noted by ancient historians in the narrative of the Second Punic War (218–201 BC). In addition to the best-known use of the weather during the Battle of Cannae (216 BC), during which Hannibal, according to historian Florus, colluded with all nature, the article analyses the failed attempt to capture Rome in 211 BC – prevented by a storm, weather prodigia heralding Roman defeat in the first part of the war as well as the function of meteorological battle imagery.